Non-Pharmacological Therapy For Adolescent Depression: Literature Review - Indra Maulana; Hesti , Hesti Platini (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2023)
ABSTRACT Introduction: Adolescence is a period of transition between childhood and adulthood, characterized by biological, cognitive, and socio-emotional changes. Most adolescents have behaved more maturely as they have become aware of a new formal status, either at home or at school. Adolescents are at risk for depressive disorders due to their inability to deal with stress or pressure. To alleviate depression symptoms, pharmacological and non-pharmacological therapies can be used. The goal of this study was to conduct a literature review on non-pharmacological therapies for treating depression in adolescents. Methods: A literature review with the keywords